Fe-Ni ALLOY ELECTRODEPOSITION FROM SIMPLE AND COMPLEX TYPE SULFATE ELECTROLYTES CONTAINING Ni/Fe RATIO OF 1 AND 12 - Moniruzzaman, M.; Shorowordi, K.M.; Azam, A.; Taufique, M.F.N. (Journal of Mechanical Engineering, 2014)
Iron-nickel (Fe-Ni) alloy electrodeposition has been conducted from simple and complex baths having Ni/Fe ratio of 1 and 12. The applied current density varies from 30 to 100 mA/cm2. The coating composition, morphology and microhardness are measured and characterized by SEM/EDX and Shimadzu microhardness tester. The percentage of Ni in the coating increases with increasing current density and the Ni/Fe ratio of electrolytes which is supported by the alloy deposition principle. Fine grained and smooth coating without microcracking is obtained from the complex baths. Complexing agents are supposed to reduce the deposit stress developed during electrodeposition. Increase in Ni/Fe ratio in the bath as well as current density results in decreasing grain size of the deposits. High current density is believed to give rise to a high degree of adatoms at the electrode surface and high degree of adatoms decreases the grain size. Microhardness of the coating increases with the increase of bath Ni/Fe ratio as well as current density of electrodeposition. DOI: http://dx.doi.org/10.3329/jme.v44i1.19498